Toleransi Menurut Al- Qur'an dan Hadits - Ramlan Abdul Gani (Sekolah Tinggi Agama Islam Nurul Iman Bogor, 2020)
Terminology tolerance (in Arabic: tasâmuh) in Islam basically dates from Surah al-Kâfirûn. It is implied that in the life of religious there is a potential happened different perspective. Islam is aware that among non-Muslim happen in the understanding that her religion the right same with the Muslims feel that way. The all supposition the truth in each is something necessity to remain consistent in following a get it. Religion or get it considers himself indeed a habitude. If not, people will tied to uncertainty confidence. However, if there is no tolerance, religious people are also people whom apologis and arrogant. How many from among all religions dare to die for maintaining the truth religion are foolhardy. This is because people do not gives space to all else to live in side by side, as if it is entitled to hold the right. Command martyred (mati syahid) to maintain the truth islamic it is true that. However, it must be performed when the people in the time of his distress for example in a condition are attacked. In the condition of peace, islamic obliging him to give space and even help each other. Give space to live to the followers other that is the form of tolerance.